Digital Object Identifier (DOI) viabilizando a via verde - Coutinho-Marques, Paulo Eduardo Potyguara; Magarinos-Torres, Rachel; Carvalho, Maria da Conceição Rodrigues de; Vasconcellos, Marcelo Simão de; Mena-Chalco, Jesús; Guimarães, Maria Cristina Soares (Cadernos BAD, 2014)
Digital Object Identifier (DOI) viabilizando a via verde